Türkiye Faunası İçin Yeni Bir Enochrus Thomson, 1859 (Coleoptera: Hydrophilidae) Kaydı - Polat, A.; Taşar, G. E.; İncekara, Ü. (Fırat University, 2015)
Türkiye Hydrophilidae faunası için yeni bir kayıt olan Enochrus calabricus (Ferro, 1986), İç Anadolu Bölgesi (Kayseri, Türkiye) den kaydedildi. Türün ekolojik bulguları ve morfolojik karakterleri tanımlandı ve erkek genitalyası resimlerle gösterildi. Yeni tür için biyolojik gözlemler ve dağılım kayıtları da sunuldu. Teşhise ait karakterler electron mikroskobu mikrofotoğrafları ile desteklendi.

A new record of the Hydrophilids, Enochrus calabricus (Ferro, 1986), is recorded from central Anatolia (Kayseri, Turkey). The ecological findings and morphological characters of the species are described and its aedeagus figure illustrated. Biological observations and distribution records for the new record is also presented. Diagnostic characters are supported with electron micrographs.
A New Record of Enochrus Thomson, 1859 (Coleoptera: Hydrophilidae) for the Turkish Fauna